P88 Identifying risk factors for multiple revisional lumbar spine surgery. Issue 3 (14th February 2019) - El Sheikh, M; Badran, K; Kouli, O; Abdelsadg, M; Fadelalla, M; Hossain-Ibrahim, K
Abstract : Objectives: Recurrent lumbar spine surgery due to disc herniation is a contributor to debilitating pain, disability, and carries a high patient morbidity rate 1 We identified risk factors for recurrent lumbar disc herniation post-surgical intervention. Design: Retrospective Cohort Study. Subjects: All adult lumbar spine revisions for disc herniation performed in the Neurosurgical Department at Ninewells Hospital. Methods: The number of revisions from 2013 to 2017 for each patient was recorded and two groups were identified. The first group consisted of patients who had one revision and the second group consisted of patients who had recurrent revisions (more than one) Possible factors influencing the likelihood of recurrent revisions were also noted, including age, gender, BMI, operation length, level of surgery, time from primary surgery to revision, smoking and diabetes status. Results: 140 patients had revision surgeries, of which 87 (62.1%) had one revision while 53 (37.1%) had recurrent operations. Younger patients (p=0.025) and patients with higher BMI (p=0.01) were more likely to have a higher number of revisions. Patients with DM (p=0.015) were associated with a higher likelihood of recurrent revisions. Other factors had little effect on the likelihood of recurrent revisions (p>0.05). Conclusions: Identifying risk factors that influence the recurrence of lumbar revisions helps improve patient outcome and decrease incidence of revisions.